Analysis of 4999 Online Physician Ratings Indicates That Most Patients Give Physicians a Favorable Rating - Kadry, Bassam; Chu, Larry F; Kadry, Bayan; Gammas, Danya; Macario, Alex (JMIR Publications, 2011)
BackgroundMany online physician-rating sites provide patients with information about physicians and allow patients to rate physicians. Understanding what information is available is important given that patients may use this information to choose a physician. ObjectivesThe goals of this study were to (1) determine the most frequently visited physician-rating websites with user-generated content, (2) evaluate the available information on these websites, and (3) analyze 4999 individual online ratings of physicians. MethodsOn October 1, 2010, using Google Trends we identified the 10 most frequently visited online physician-rating sites with user-generated content. We then studied each site to evaluate the available information (eg, board certification, years in practice), the types of rating scales (eg, 1-5, 1-4, 1-100), and dimensions of care (eg, recommend to a friend, waiting room time) used to rate physicians. We analyzed data from 4999 selected physician ratings without identifiers to assess how physicians are rated online. ResultsThe 10 most commonly visited websites with user-generated content were HealthGrades.com, Vitals.com, Yelp.com, YP.com, RevolutionHealth.com, RateMD.com, Angieslist.com, Checkbook.org, Kudzu.com, and ZocDoc.com. A total of 35 different dimensions of care were rated by patients in the websites, with a median of 4.5 (mean 4.9, SD 2.8, range 1-9) questions per site. Depending on the scale used for each physician-rating website, the average rating was 77 out of 100 for sites using a 100-point scale (SD 11, median 76, range 33-100), 3.84 out of 5 (77%) for sites using a 5-point scale (SD 0.98, median 4, range 1-5), and 3.1 out of 4 (78%) for sites using a 4-point scale (SD 0.72, median 3, range 1-4). The percentage of reviews rated ≥75 on a 100-point scale was 61.5% (246/400), ≥4 on a 5-point scale was 57.74% (2078/3599), and ≥3 on a 4-point scale was 74.0% (740/1000). The patient's single overall rating of the physician correlated with the other dimensions of care that were rated by patients for the same physician (Pearson correlation, r = .73, P < .001). ConclusionsMost patients give physicians a favorable rating on online physician-rating sites. A single overall rating to evaluate physicians may be sufficient to assess a patient's opinion of the physician. The optimal content and rating method that is useful to patients when visiting online physician-rating sites deserves further study. Conducting a qualitative analysis to compare the quantitative ratings would help validate the rating instruments used to evaluate physicians.